3w+6(w-5)=-12

Simple and best practice solution for 3w+6(w-5)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3w+6(w-5)=-12 equation:


Simplifying
3w + 6(w + -5) = -12

Reorder the terms:
3w + 6(-5 + w) = -12
3w + (-5 * 6 + w * 6) = -12
3w + (-30 + 6w) = -12

Reorder the terms:
-30 + 3w + 6w = -12

Combine like terms: 3w + 6w = 9w
-30 + 9w = -12

Solving
-30 + 9w = -12

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 9w = -12 + 30

Combine like terms: -30 + 30 = 0
0 + 9w = -12 + 30
9w = -12 + 30

Combine like terms: -12 + 30 = 18
9w = 18

Divide each side by '9'.
w = 2

Simplifying
w = 2

See similar equations:

| p=9*3.14*u | | 5y=-50y | | 2v+6=13v-4v+62 | | 5(2x-13)=-25 | | 3n^2-16n+5=0 | | c=-10.5 | | 9x^2-30=3x | | 74=6-x | | ln-m=ln(m+10) | | Q+16=144 | | 2.2=-6y+40.6 | | 2(4x-3)/34 | | -7u+11u+5=2u+31 | | X^2-7x+12=y | | 11x+5X-1=65X-26 | | 3x^5-6x^4+18x^3= | | 28b^2-2b-6=0 | | -38m^4n^16/19n^18p^3 | | ln-5n=ln(4-3n) | | 9y-4y=35 | | 6x+5-3x=28 | | 8x+32-43x=77-12x | | u^2-14u+48=0 | | 4y-(3+y)y=2 | | 3x+55=115 | | 7x-5=3(4x+5) | | -8ln-9x=-8 | | -5m-4+[3]=13 | | y-12=3y-25 | | x^2-4w-35=0 | | A^2-17ab+60b^2=0 | | 6v^2-26=-v |

Equations solver categories